Reigniting the Flame of Change: The Resurgence of Iran’s Radical Feminist Movement in the Aftermath of Mahsa Ahmini’s Death - Hergianasari, Putri; Wijanarka, Tunjung (Journal Of Middle East and Islamic Studies, 2023)
This article explores the significant impact of the radical feminist movement in Iran following the tragic death of Mahsa Ahmini. This incident sparked widespread international protests and shed light on the unjust treatment of women in Iran. The study employs a qualitative research method with descriptive analysis, and the authors use library research for the collection of data. The findings of this research reveal that the radical feminist movement in Iran has gained strength since Mahsa Ahmini’s passing, marked by numerous demonstrations led by feminist activists advocating for justice and reforms in the discriminatory legal framework. This movement fights for women’s rights, including political and public participation and the right to make decisions about their own lives. The research conclusion underscores the role of social media and technology in bolstering the radical feminist movement in Iran, facilitating information access and communication. Nevertheless, the movement faces formidable challenges, including threats and harassment from authorities and a society that still objectifies and marginalizes women. Consequently, this research underscores the crucial role of the radical feminist movement in driving change and reshaping the societal and legal systems that perpetuate gender discrimination in Iran.